â€œMANGGULLUâ€ MAKANAN KHAS LOKAL BERBASIS BUAH PISANG DAN KACANG TANAH - Naema Bora (Partner, 2009)
â€œManggulluâ€ Local Special Food Based On Banana And Peanut. For the agenda of diversivikasi [by] food material, potential traditional food products of local standard barium needed alwaysly in diging and developed. Because local food products generally has niulai taste goal that is typical and doesn't contain chemicals endangering for consuming it. Manggullu is one ofÂ  local typical food type of sub-province public Sumba Timur, made from banana jam and peanut boxed collectively/together causing forms a dough. Sees light f ood potency which pertained this on unique hence this research done.This research applies Completely randomized design method. Treatment tried consisted of banana type and composition of peanut and design as unique f actor with formation ofÂ  treatment as follows: pl p2 etc.: banana ambon + 250% peanut, plp2 etc.: banana ambon + 50% peanut, P3: banana ambon + 75% peanut, P4:banana beraga + 25% peanut, P5 : banana is having Beraga + 50% peanut, P6:banana beraga + 75% peanut, P7 : banana kepok + 25% peanut, P8: banana kepok + 50% peanut, P9: banana kepok + 75 % peanut. Each re- treatment 3 times so that as a whole there is there are 27 attempt units.Result of research indicates that treatment of banana type and composition of peanut added influential reality to quality of light food of manggullu yielded especially concerning chemical composition and character physical of product. Statistically chemical composition manggullu tarutama water activity, different f at rate and glucose rate depended f rom banana type as component of main standard and composition ofÂ  peanut added. Banana type ambon and baranga with composition 75% peanut can increase nutritional value and panelist hobby value (colour, taste goal, and aroma) to product manggullu. https://sexlocals.comKey word: Local Food, Banana, Manggullu